2017
DOI: 10.1177/0022487117696280
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Is Believing

Abstract: This study addresses the following questions: Does professional development (PD) designed to meet third-, fourth-, and fifth-grade teachers’ pedagogical and content needs influence how teachers teach and engage with graphical devices found in social studies texts? If so, what effect does that instruction and engagement have on students’ comprehension of those devices and social studies reading materials that contain them? We worked with teachers and students in a context-embedded PD series that emphasized lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
(25 reference statements)
2
16
0
6
Order By: Relevance
“…De entre las múltiples dimensiones críticas a considerar cuando se plantean tareas dirigidas a fomentar la alfabetización visual en el alumnado, Cappello (2017) destaca la autoría y propósito de la imagen, la información transmitida por la misma y la influencia del propio lector en su interpretación. Con todo, estos aspectos referidos al tratamiento crítico de las imágenes parecen adscribirse a líneas propias de la Educación Artística y Visual, lo que no impide que desde la enseñanza de la Historia o desde cualquier otra disciplina se pueda contribuir a este fin marcando como objetivo integral la alfabetización visual de los estudiantes (Brugar & Roberts, 2017;Gómez-Pintado y Marcellán, 2017). Actualmente esto tiene una especial significación en el contexto español ya que el marco curricular actual (Ley Orgánica para la Mejora de la Calidad Educativa, Gobierno de España, 2013, BOE n.º 295 -en adelante, LOMCE-) reduce drásticamente el número de horas dedicadas a Educación Artística.…”
Section: Alfabetización Visual Y Libros De Historiaunclassified
See 1 more Smart Citation
“…De entre las múltiples dimensiones críticas a considerar cuando se plantean tareas dirigidas a fomentar la alfabetización visual en el alumnado, Cappello (2017) destaca la autoría y propósito de la imagen, la información transmitida por la misma y la influencia del propio lector en su interpretación. Con todo, estos aspectos referidos al tratamiento crítico de las imágenes parecen adscribirse a líneas propias de la Educación Artística y Visual, lo que no impide que desde la enseñanza de la Historia o desde cualquier otra disciplina se pueda contribuir a este fin marcando como objetivo integral la alfabetización visual de los estudiantes (Brugar & Roberts, 2017;Gómez-Pintado y Marcellán, 2017). Actualmente esto tiene una especial significación en el contexto español ya que el marco curricular actual (Ley Orgánica para la Mejora de la Calidad Educativa, Gobierno de España, 2013, BOE n.º 295 -en adelante, LOMCE-) reduce drásticamente el número de horas dedicadas a Educación Artística.…”
Section: Alfabetización Visual Y Libros De Historiaunclassified
“…Pese a los rasgos que comparten ambas, existen diferencias evidentes entre estos dos grandes grupos de representaciones, de forma que la investigación actual continúa explorando los factores que intervienen cuando son utilizadas en situaciones de enseñanza (Stebner, Kühl, Höffler, Wirth, & Ayres, 2017). Dentro de las imágenes estáticas, las que contienen un trasfondo histórico (o imágenes históricas), como fuentes documentales que nos aproximan a lo acontecido en el pasado, tienen un papel significativo en materias como las Ciencias Sociales al permitir a los alumnos/as discutir, argumentar y contrastar información (Brugar & Roberts, 2017), de forma que un adecuado tratamiento de las mismas fomenta el desarrollo social, emocional, cognitivo y la participación que debe caracterizar a toda sociedad democrática (Cooper, 2015).…”
Section: Introductionunclassified
“…Most research on visual literacy has been carried out in the natural science domain (Slough, McTigue, Kim, & Jennings, 2010;Wright, McTigue, Eslami, & Reynolds, 2014;Yeh & McTigue, 2009). The limited research that we found in social studies has concerned how younger students understand the variety of graphics they encounter (Brugar & Roberts, 2017;Gregg, 1997), which is an important focus given the high frequency in content texts (Fingeret, 2012). Nevertheless, this focus has limited research primarily to receptive comprehension at different grade levels (Arizpe & Styles, 2003;Brugar & Roberts, 2017;McTigue & Flowers, 2011;Walsh, 2006).…”
Section: What Do We Know About Students' Use Of Graphical Representatmentioning
confidence: 99%
“…The limited research that we found in social studies has concerned how younger students understand the variety of graphics they encounter (Brugar & Roberts, 2017;Gregg, 1997), which is an important focus given the high frequency in content texts (Fingeret, 2012). Nevertheless, this focus has limited research primarily to receptive comprehension at different grade levels (Arizpe & Styles, 2003;Brugar & Roberts, 2017;McTigue & Flowers, 2011;Walsh, 2006). Although graphical representations have the potential to aid comprehension (Carney & Levin, 2002;Duke et al, 2013;Norman, 2012), both children and adults can experience difficulties in understanding them (Shah & Hoeffner, 2002).…”
Section: What Do We Know About Students' Use Of Graphical Representatmentioning
confidence: 99%
See 1 more Smart Citation